Unlocking insights in bicuspid aortic valve management in adult patients: the vital role of cardiac imaging - Sara Di Michele; Vito Maurizio Parato; Giovanna Di Giannuario; Naji Kholaif; Mohammed Al Admawi; Saif Aljheish; Lana Arbili; Amal Alshammari; Andrea Giovanni Parato; Hani Al sergani (Monaldi Archives for Chest Disease, 2023)
The bicuspid aortic valve (BAV) presents a multifaceted clinical challenge due to its diverse morphologies and associated complications. This review aims to elucidate the critical role of cardiac imaging in guiding optimal management strategies for BAV patients. BAV, with a prevalence of 1% to 2%, has genetic underpinnings linked to the NOTCH1 gene mutation. Variability in BAV morphology necessitates tailored surgical approaches. The three primary types of BAV morphology - right-left cusp fusion, right-noncoronary cusp fusion, and left-noncoronary cusp fusion - demand nuanced considerations due to their distinct implications. Valvular dysfunction results in aortic stenosis or regurgitation, attributed to altered valve structure and turbulent hemodynamics. Cardiac imaging modalities, including echocardiography, magnetic resonance imaging, and computerized tomography, are instrumental in assessing valve function, aortic dimensions, and associated complications. Imaging helps predict potential complications, enabling informed treatment decisions. Regular follow-up is crucial to detecting alterations early and intervening promptly. Surgical management options encompass aortic valve repair or replacement, with patient-specific factors guiding the choice. Post-surgical surveillance plays a vital role in preventing complications and optimizing patient outcomes. The review underscores the significance of advanced cardiac imaging techniques in understanding BAV's complexities, facilitating personalized management strategies, and improving patient care. By harnessing the power of multimodal imaging, clinicians can tailor interventions, monitor disease progression, and ultimately enhance the prognosis and quality of life for individuals with BAV.